Recreational microplastics as emerging pollutants: effects of crumb rubber leachate across ecosystems - Sharon T. Pochron; Xiayan Ye; Amith S. Maroli; Arjun K. Venkatesan; Samy Sasoun; Thomas J. Gaylor; Mary Girgis; Morgan A. Jacobellis; Alec Miranda; Johanna A. Mitra; Grace Van Gelder; Samantha H. Byrne; et al. (Chemosphere, 2026)

A spatial, agent-based model to explore mechanisms of bluetongue virus persistence at the interface of domestic and wildlife ruminant populations - Geonsik Yu; Carly Barbera; Mollie Burton; Jeremy Alder; George Wittemyer; Christie Mayo; T. Alex Perkins (Ecological Modelling, 2026)

Soil moisture mapping using radio signal strength and gaussian process regression - Hongjun Yu; Erik Muller; Alex McBratney; Salah Sukkarieh (Precision Agriculture, 2026)
Background Soil moisture is a key variable in precision agriculture, affecting irrigation management, crop productivity, and water-use efficiency. However, field-scale soil moisture monitoring remains challenging because conventional sensing approaches are often costly and provide limited spatial coverage. This study proposes a simulation-based framework for soil moisture mapping that integrates near-ground radio-frequency (RF) sensing, Gaussian Process Regression (GPR), and adaptive sample selection Methods Received signal strength (RSS) measurements obtained from paired RF sensors were used as path-averaged proxies for soil moisture. GPR was employed to reduce measurement noise and reconstruct spatial soil moisture distributions from sparse ground-truth observations. An error-driven adaptive sampling strategy was developed to identify locations for additional soil moisture measurements under constrained sampling budgets. The framework was evaluated using numerical simulations based on synthetic soil moisture fields with varying levels of spatial variability and measurement noise. Results Simulation results demonstrated that the proposed framework reduced soil moisture estimation error compared with random sampling and conventional GPR interpolation when only a limited number of samples were available. The adaptive sampling strategy improved the efficiency of data collection by prioritizing regions with higher prediction uncertainty. Reconstruction accuracy was influenced by both soil moisture variability and measurement noise, highlighting the importance of sensor quality and field heterogeneity in system performance. Conclusion The study demonstrates the potential of combining RSS-based RF sensing, probabilistic regression, and adaptive sampling for low-cost and scalable soil moisture mapping in precision agriculture. Although the framework was evaluated only under idealized simulation conditions and no field validation was conducted, the results provide proof of concept and support future development, field testing, and extension of the approach for practical agricultural applications.

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Corrigendum to ‘Cytochrome CYP72A15 may play a role in metabolic resistance to mesotrione in wild radish’ [Pesticide Biochemistry and Physiology Volume 210 (2025) 106380] - Feng-Yan Zhou; Huan Lu; Xueping Huang; Yunjing Han; Yong Zhang; Heping Han; Liudmyla Tsykalchuk; Alex Nyporko; Qin Yu (Pesticide Biochemistry and Physiology, 2026)

Future humidex extremes over North America: projections and uncertainties from the CanESM5 large ensemble - Bin Yu; Alex J. Cannon; Dae Il. Jeong (Climate Dynamics, 2026)
Extreme heat poses growing risks to human health, ecosystems, agriculture, and infrastructure under global warming. While most studies emphasize air temperature, the humidex, which combines temperature and humidity, better captures human-perceived heat stress. This study assesses historical and projected changes in the 95th percentile of daily humidex (HX95) across North America using ERA5 reanalysis and the Canadian Earth System Model version 5 (CanESM5) single-model initial-condition large ensemble. By integrating observations with climate simulations under multiple emission scenarios, we quantify externally forced changes and uncertainties from internal variability. Results reveal a pronounced latitudinal gradient, with HX95 highest in the southern U.S. and Mexico and lowest in northern and mountainous regions. At 2 °C and 3.5 °C of global warming above the pre-industrial level, North American mean HX95 rises by about 2.6 and 5.8 units, respectively, relative to 1995–2014, with widespread expansion of areas exceeding hazardous thresholds. Responses are robust and only weakly dependent on emission scenario, as inter-scenario differences remain small at fixed warming levels. Increases stem from higher temperatures, enhanced moisture, and poleward circulation shifts. Internal variability contributes substantially to regional uncertainty, particularly in northern North America, but externally forced changes dominate, with signal-to-noise ratios above 3 at 2 °C and 6 at 3.5 °C. Overall, humidex extremes are projected to intensify and migrate poleward with continued global warming. Limiting warming to 2 °C rather than 3.5 °C would significantly reduce exposure to dangerous heat, underscoring the urgency of mitigation and adaptation.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Atmospheric circulation and moisture budget drivers of dominant modes of winter extreme precipitation variability over North America - Dae Il Jeong; Bin Yu; Alex J. Cannon (Climate Dynamics, 2026)
Multi-day winter precipitation events can trigger hazards like flooding and landslides. This study identifies dominant modes of variability—and large-scale dynamical, thermodynamical, and moisture budget drivers—of monthly maximum consecutive 5-day precipitation extremes (Rx5day) across North America (NA) during extended winter months (November–March, 1961–2023). Three dominant modes of Rx5day variability, collectively accounting for 30.7% of total variance, are identified from two global reanalysis datasets (ERA5 and JRA-55) using common Empirical Orthogonal Function (EOF) analysis. Distinct positive and negative anomaly centers are found across western and eastern NA. The three modes are primarily driven by large-scale atmospheric circulation anomalies, extending from the North Pacific across NA to the North Atlantic, and atmospheric moisture anomalies, particularly wind-driven moisture transport concentrated in the lower troposphere (surface to ~ 500 hPa). This is reflected in anomalous westerly and southerly flows bringing moisture from the Pacific into western NA and from the Gulf of Mexico into southeastern NA, where upward motion and deep tropospheric moisture columns enhance extreme precipitation. Moisture budget analysis reveals that moisture flux convergence primarily supplies moisture for these extreme events, with local evaporation playing a minor role. Specifically, convergence of mean moisture by transient winds emerges as the primary driver of extreme precipitation variability, with its contribution often exceeding that of total moisture flux convergence. Moisture budget components at 850 hPa closely reflect their vertically integrated counterparts, indicating the pivotal role of the lower troposphere in large-scale moisture transport and convergence processes for extreme precipitation.

Shallow seasonal stratification ameliorates coral bleaching during record-breaking marine heatwaves in a marginal subtropical system - Gonzalo Pérez-Rosales; Yu-De Pei; Joshua Bennett-Williams; Timothy B. King; Markus Rummel; Tzu Hao Chung; Alex S. J. Wyatt (Coral Reefs, 2026)
Marine heatwaves are intensifying globally, with the Fourth Global Coral Bleaching Event (GCBE) beginning in 2023, yet coral bleaching outcomes remain highly variable across space and time. This study examines the role of fine-scale thermal variation in shaping bleaching impacts during two record-breaking marine heatwaves (2022 and 2024) affecting shallow coral assemblages in the marginal and urbanised environments of Hong Kong. Using high-resolution in situ temperature loggers, we quantified thermal exposure across coral-inhabited depths (1–8 m) at three sites and related this to bleaching prevalence across taxa. In 2024, surface temperatures exceeded the local bleaching threshold (29.7 °C) for 37 days, resulting in heat accumulation that reached 25.2 °C days (9.24 °C weeks) and remained above 8 °C days (°C weeks) for 46 days (20 days). However, seasonal stratification created vertical gradients of up to 9.6 °C between 2 and 8 m, reducing the magnitude and duration of heat accumulation severalfold (e.g., up to 35.4 °C days and 76 days > 8 °C days at 2 m, compared to 7.9 °C days at 8 m). Bleaching prevalence was 20–46% lower between 1 and 5 m, with Bayesian bleaching probabilities highest for Goniopora (82%) and lowest for Porites (64%). These patterns could not be explained by satellite-derived sea surface temperatures alone. Despite record heating and stress, mortality was limited (60 to 95% pigmentation recovery). Our findings provide rare fine-scale assessments of bleaching and thermal dynamics, including during the Fourth GCBE, and highlight how local stratification can create thermal refuges. Understanding how oceanographic contexts structure these refuges is essential for identifying and conserving coral communities with greater survival potential under accelerating ocean heating.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Global ocean indicators: Marking pathways at the science-policy nexus - Karina von Schuckmann; Alex Godoy-Faundez; Véronique Garçon; Frank E. Muller-Karger; Karen Evans; Ward Appeltans; Narissa Bax; Lisandro Benedetti Cecchi; Anthony Bernard; Kim Bernard; Jarret Byrnes; Gabrielle Canonico; et al. (Marine Policy, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Real-time soil moisture mapping using scalable RF sensor networks - Hongjun Yu; Erik Muller; Alex Mcbratney; Salah Sukkarieh (Computers and Electronics in Agriculture, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Leukocyte telomere length and risk of heart failure with preserved ejection fraction in high-risk Chinese patients with hypertension under 65 years - Alian Zhang; Zhengde Tang; Alex Chia Yu Chang; Jun Gu; Junfeng Zhang; Yang Zhuo; Huili Zhang (GeroScience, 2025)

Rapid detection of microplastics and nanoplastics in seconds by mass spectrometry - Mengyuan Xiao; Yongqing Yang; Hanin Alahmadi; Allison Harbolic; Gina M. Moreno; Terry Yu; Jerry Liu; Alex Guo; Genoa R. Warner; Phoebe A. Stapleton; Hao Chen (Journal of Hazardous Materials, 2025)

Evaluation of allelic ratio distortion in haploid cells using single cell multiome data of the pig testicle - Yu Lian; Johannes Liebig; Laia Marín-Gual; Aurora Ruiz-Herrera; Craig Lewis; Eduardo Rodriguez; Armand Sanchez; Sören Lukassen; Christian Conrad; Alex Clop (Animal Reproduction Science, 2025)

Redefining Swiss Territorial Typologies: An Unsupervised Learning Approach to the Rural–Urban Continuum - Marj Tonini; Jingyan Yu; Alex Hagen-Zanker (Journal of Geovisualization and Spatial Analysis, 2025)
Urban expansion in Europe has accelerated over recent decades, significantly blurring the boundaries between urban and rural landscapes and giving rise to extensive peri-urban areas. These dynamic transformations demand timely and effective landscape classifications to track environmental, demographic, and socio-economic developments and for a deeper understanding of human settlements and their sustainability impacts. Traditional threshold-based classification methods, while widely used, rely heavily on expert knowledge and require substantial human input, posing challenges for rapid updates to rural–urban classifications. This study addresses these limitations by leveraging an unsupervised learning neural network to classify territorial typologies in Switzerland at a granular municipal level. Using a comprehensive dataset that integrates physical, demographic, and socio-economic variables, we identified six distinct clusters, which were subsequently mapped onto the geographical space, providing a characterization of the Swiss landscape through its intricate rural–urban interface, urban expansion frontiers, and aging populations in peri-urban and rural areas. Our analysis also highlights critical phenomena such as agricultural land loss and the encroachment into ecologically sensitive Alpine territories. Graphical outputs, such as heatmaps and boxplots, were used as effective visual tools to aid in results interpretation, uncover variables distributions and relationships, and enhance the analytical process. The findings demonstrate that clustering procedures based on unsupervised machine learning provide valuable insights into rural–urban configurations and contemporary urbanization processes, offering a robust framework for studying the interplay between human settlements and environmental sustainability, particularly in vulnerable Alpine regions.

Cytochrome CYP72A15 may play a role in metabolic resistance to mesotrione in wild radish - Feng-Yan Zhou; Huan Lu; Xueping Huang; Yunjing Han; Yong Zhang; Heping Han; Liudmyla Tsykalchuk; Alex Nyporko; Qin Yu (Pesticide Biochemistry and Physiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Comparison of two distinct leading modes in the variability of summer humidex and temperature heatwaves over North America - Dae Il Jeong; Bin Yu; Alex J. Cannon (Climate Dynamics, 2025)
Continuous hot and humid conditions pose greater health risks than heat alone, making it crucial to distinguish between temperature-driven and humidity-amplified heat stress. The variability of monthly humidex and temperature heatwaves over North America (NA) is compared for extended summers (June-September) from 1951 to 2022. Two distinct leading modes are identified for both humidex and temperature heatwaves over NA using empirical orthogonal function (EOF) analysis, collectively explaining 31% and 27% of total variance, respectively. These two leading modes, exhibiting a phase shift due to their orthogonality, are associated with large-scale atmospheric wave trains extending from the North Pacific to NA. This results in atmospheric pressure anomalies across the continent, driving notable differences in the variability of both heatwaves over NA. Atmospheric moisture transported from the North Pacific to NA also affects the development of both heatwaves, with more pronounced moisture anomalies observed for humidex heatwaves, highlighting a key distinction in the large-scale atmospheric circulation between humidex and temperature heatwaves. Positive phases of both heatwaves are associated with an anticyclonic anomaly, which leads to anomalous descent, reduced total cloud cover, above-normal surface radiation heating, and below-normal surface relative humidity over NA. Atmospheric moisture acts as a greenhouse gas to absorb longwave radiation, leading to increased downward longwave radiation. However, these physical processes exhibit weaker feedback with humidex heatwave variability across the two distinct modes, indicating the complexity of these interactions involving intensified cloud cover, surface humidity, and latent heat release due to significant atmospheric moisture injected into the regions of NA.

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Is ignorance bliss? Evaluating information awareness and life satisfaction through the lens of perceived air pollution: The case of Beijing, China - Xiaohan Yu; Yanting Fan; Joon Sik Kim; Hyungchul Chung; Alex Lord; Richard Dunning (Journal of Environmental Management, 2024)

Genomic, transcriptomic and epigenomic analysis towards the understanding of porcine semen quality traits. Past, current and future trends - Pedro Sa; Marta Gòdia; Nicole Lewis; Yu Lian; Alex Clop (Animal Reproduction Science, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

O-GlcNAc modification of GSDMD attenuates LPS-induced endothelial cells pyroptosis - Fan Yu; Zhen Zhang; Yiping Leng; Alex F. Chen (Inflammation Research, 2024)
Objective Increased O -linked β- N -acetylglucosamine ( O -GlcNAc) stimulation has been reported to protect against sepsis associated mortality and cardiovascular derangement. Previous studies, including our own research, have indicated that gasdermin-D(GSDMD)-mediated endothelial cells pyroptosis contributes to sepsis-associated endothelial injury. This study explored the functions and mechanisms of O -GlcNAc modification on lipopolysaccharide (LPS)-induced pyroptosis and its effects on the function of GSDMD. Methods A LPS-induced septic mouse model administrated with O -GlcNAcase (OGA) inhibitor thiamet-G (TMG) was used to assess the effects of O -GlcNAcylation on sepsis-associated vascular dysfunction and pyroptosis. We conducted experiments on human umbilical vein endothelial cells (HUVECs) by challenging them with LPS and TMG to investigate the impact of O -GlcNAcylation on endothelial cell pyroptosis and implications of GSDMD. Additionally, we identified potential O -GlcNAcylation sites in GSDMD by utilizing four public O -GlcNAcylation site prediction database, and these sites were ultimately established through gene mutation. Results Septic mice with increased O -GlcNAc stimulation exhibited reduced endothelial injury, GSDMD cleavage (a marker of pyroptosis). O -GlcNAc modification of GSDMD mitigates LPS-induced pyroptosis in endothelial cells by preventing its interaction with caspase-11 (a human homologous of caspases-4/5). We also identified GSDMD Serine 338 (S338) as a novel site of O -GlcNAc modification, leading to decreased association with caspases-4 in HEK293T cells. Conclusions Our findings identified a novel post-translational modification of GSDMD and elucidated the O -GlcNAcylation of GSDMD inhibits LPS-induced endothelial injury, suggesting that O -GlcNAc modification-based treatments could serve as potential interventions for sepsis-associated vascular endothelial injury.

Outcome-Based blind tests for leakage diagnosis in underground watermains by acoustic technologies - Wallace Wai-Lok Lai; Tom Chun-Wai Lau; Alex Yu-Ching Cheng; Panda Kai-Chun Liu; Joseph Wang-Chi Leung (Tunnelling and Underground Space Technology, 2023)

Systematic evidence on migrating and extractable food contact chemicals: Most chemicals detected in food contact materials are not listed for use - Birgit Geueke; Ksenia J. Groh; Maricel V. Maffini; Olwenn V. Martin; Justin M. Boucher; Yu-Ting Chiang; Frank Gwosdz; Phoenix Jieh; Christopher D. Kassotis; Paulina Łańska; John Peterson Myers; Alex Odermatt; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Mechanical Behaviour of Lump-Grout Backfill Material for Underground Spaces - Hongchao Zhao; Ting Ren; Alex Remennikov; Baiyun Yu (Geotechnical and Geological Engineering, 2023)

Intercellular mitochondrial component transfer triggers ischemic cardiac fibrosis - Chan Zhang; Hao Hao; Yishi Wang; Nan Mu; Wenhua Jiang; Zihui Zhang; Yue Yin; Lu Yu; Alex Chia Yu Chang; Heng Ma (Science Bulletin, 2023)

Thermal degradation of thaumatin at low pH and its prevention using alkyl gallates - Benjamin Pomon; Yu Zhao; Alex L. Lai; Tiantian Lin; Jack H. Freed; Alireza Abbaspourrad (Food Hydrocolloids, 2023)

Land use effects on soil protists and their top-down regulation on bacteria and fungi in soil profiles - Peipei Xue; Budiman Minasny; Alex McBratney; Yuji Jiang; Yu Luo (Applied Soil Ecology, 2023)

Distinctive role of soil type and land use in driving bacterial communities and carbon cycling functions down soil profiles - Peipei Xue; Budiman Minasny; Alex McBratney; Neil L. Wilson; Yijia Tang; Yu Luo (CATENA, 2023)

Integrating oculomics with genomics reveals imaging biomarkers for preventive and personalized prediction of arterial aneurysms - Yu Huang; Cong Li; Danli Shi; Huan Wang; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Yijun Hu; Shulin Tang; Shunming Liu; Songyuan Luo; et al. (EPMA Journal, 2023)
Objective Arterial aneurysms are life-threatening but usually asymptomatic before requiring hospitalization. Oculomics of retinal vascular features (RVFs) extracted from retinal fundus images can reflect systemic vascular properties and therefore were hypothesized to provide valuable information on detecting the risk of aneurysms. By integrating oculomics with genomics, this study aimed to (i) identify predictive RVFs as imaging biomarkers for aneurysms and (ii) evaluate the value of these RVFs in supporting early detection of aneurysms in the context of predictive, preventive and personalized medicine (PPPM). Methods This study involved 51,597 UK Biobank participants who had retinal images available to extract oculomics of RVFs. Phenome-wide association analyses (PheWASs) were conducted to identify RVFs associated with the genetic risks of the main types of aneurysms, including abdominal aortic aneurysm (AAA), thoracic aneurysm (TAA), intracranial aneurysm (ICA) and Marfan syndrome (MFS). An aneurysm-RVF model was then developed to predict future aneurysms. The performance of the model was assessed in both derivation and validation cohorts and was compared with other models employing clinical risk factors. An RVF risk score was derived from our aneurysm-RVF model to identify patients with an increased risk of aneurysms. Results PheWAS identified a total of 32 RVFs that were significantly associated with the genetic risks of aneurysms. Of these, the number of vessels in the optic disc (‘ntreeA’) was associated with both AAA ( β = −0.36, P = 6.75e−10) and ICA ( β = −0.11, P = 5.51e−06). In addition, the mean angles between each artery branch (‘curveangle_mean_a’) were commonly associated with 4 MFS genes ( FBN1 : β = −0.10, P = 1.63e−12; COL16A1 : β = −0.07, P = 3.14e−09; LOC105373592 : β = −0.06, P = 1.89e−05; C8orf81/LOC441376 : β = 0.07, P = 1.02e−05). The developed aneurysm-RVF model showed good discrimination ability in predicting the risks of aneurysms. In the derivation cohort, the C -index of the aneurysm-RVF model was 0.809 [95% CI: 0.780–0.838], which was similar to the clinical risk model (0.806 [0.778–0.834]) but higher than the baseline model (0.739 [0.733–0.746]). Similar performance was observed in the validation cohort, with a C -index of 0.798 (0.727–0.869) for the aneurysm-RVF model, 0.795 (0.718–0.871) for the clinical risk model and 0.719 (0.620–0.816) for the baseline model. An aneurysm risk score was derived from the aneurysm-RVF model for each study participant. The individuals in the upper tertile of the aneurysm risk score had a significantly higher risk of aneurysm compared to those in the lower tertile (hazard ratio = 17.8 [6.5–48.8], P = 1.02e−05). Conclusion We identified a significant association between certain RVFs and the risk of aneurysms and revealed the impressive capability of using RVFs to predict the future risk of aneurysms by a PPPM approach. Our finds have great potential to support not only the predictive diagnosis of aneurysms but also a preventive and more personalized screening plan which may benefit both patients and the healthcare system. Graphical abstract

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

Prenatal exposure to polycyclic aromatic hydrocarbons is not associated with behavior problems in preschool and early school-aged children: A prospective multi-cohort study - Erin R. Wallace; Erin Buth; Adam A. Szpiro; Yu Ni; Christine T. Loftus; Erin Masterson; Drew B. Day; Bob Z. Sun; Alexis Sullivan; Emily Barrett; Ruby HN. Nguyen; Morgan Robinson; et al. (Environmental Research, 2023)

Climate change impacts on linkages between atmospheric blocking and North American winter cold spells in CanESM2 and CanESM5 - Dae Il Jeong; Bin Yu; Alex J. Cannon (Climate Dynamics, 2023)
This study investigates changes in linkages between atmospheric blocking and winter (December–February) cold spells over the Pacific-North America region in two large-ensembles of Canadian Earth System Models (CanESM2 and CanESM5 under high-emission scenarios). The two ensembles show decreases in winter blocking frequency over the North Pacific from 1981–2010 baseline to 2071–2100, with larger decreases in CanESM5 (− 3.08%/decade) than CanESM2 (− 1.73%/decade). Using a time-invariant (stationary) threshold estimated from the baseline to define cold days, the two ensembles project a decline in cold spell events as future air temperature increases; the occasional occurrence of cold spell events is still projected to occur at the end of the century. Using a time-dependent (nonstationary) climatological threshold, CanESM2 and CanESM5 ensembles project modest decreases in cold spell days over North America (− 2.0 and − 2.3%/decade). With the nonstationary threshold, the two ensembles project decreases in winter cold spell frequency during blocking, with larger decreases in CanESM5 (13%) than CanESM2 (3%) for 2071–2100 period compared to the baseline. The two ensembles display similar blocking-cold spell linkages between the baseline and future periods; however, the linkage is weaker and exhibits larger uncertainty in the future. Moreover, temperature advection and net heat flux anomalies during blocking are generally weaker for the future period, resulting in weaker impacts on North American cold spells with larger uncertainty associated with increases in internal-variability.

Influences of atmospheric blocking on North American summer heatwaves in a changing climate: a comparison of two Canadian Earth system model large ensembles - Dae II Jeong; Alex J. Cannon; Bin Yu (Climatic Change, 2022)
As summer heatwaves have severe adverse impacts on human society and ecosystems, there is need to better understand their meteorological drivers and future projections under climate change. This study investigates the linkage between atmospheric blocking and summer (June–August) heatwaves over North America using two reanalysis datasets (ERA-Interim and NCEP-DOE-R2) and two large-ensembles of Canadian Earth System Models (CanESM2 and CanESM5) for the 1981–2010 baseline period as well as projected changes under high-emission scenarios out to 2071–2100. Compared to NCEP-DOE-R2, both ensembles underestimate summer blocking frequency in the north Pacific, Alaska, and western Canada (by − 37%), while CanESM2 ensemble also underestimates blocking frequency in central and eastern Canada (by − 36%). CanESM5 generally shows better performance than CanESM2 in its reproduction of blocking frequency over central and eastern Canada, which is consistent with its overall improvements in simulating large-scale climate patterns. The two ensembles, however, agree with the reanalyses in their blocking-heatwave linkages. Above-normal heatwave frequency occurs in the blocking core and its surroundings due to positive heat flux anomalies, while below-normal frequency occurs at remote locations on the eastern and/or southern flanks of the blocking core due to cold air temperature advection anomalies. Future projections in central Canada differ between the models, largely due to the significant under-representation of blocking frequency by CanESM2. However, the two ensembles generally project similar behavior between the baseline and future period for spatial distributions of blocking-heatwave linkages, indicating blocking will continue to play an important role in the development of summer heatwaves in the future.

Links between atmospheric blocking and North American winter cold spells in two generations of Canadian Earth System Model large ensembles - Dae Il Jeong; Bin Yu; Alex J. Cannon (Climate Dynamics, 2021)
Due to the significant negative consequences of winter cold extremes, there is need to better understand and simulate the mechanisms driving their occurrence. The impact of atmospheric blocking on winter cold spells over North America is investigated using ERA-Interim and NCEP-DOE-R2 reanalyses for 1981–2010. Initial-condition large-ensembles of two generations of Canadian Earth System Models (CanESM5 and its predecessor, CanESM2) are evaluated in terms of their ability to represent the blocking-cold spell linkage and the associated internal-variability. The reanalysis datasets show that 72 and 58% of cold spells in southern and northern North America coincide with blocking occurring in the high-latitude Pacific-North America. Compared to the two reanalyses, CanESM2 and CanESM5 ensembles underestimate by 19.9 and 14.3% cold spell events coincident with blocking, due to significant under-representation of blocking frequency over the North Pacific (− 47.1 and − 29.0%), whereas biases in cold spell frequency are relatively small (6.6 and − 4.7%). In the reanalyses, regions with statistically significant above-normal cold spell frequency relative to climatology lie on the east and/or south flanks of blocking events, whereas those with below-normal frequency lie along the core or surrounding the blocking. The two ensembles reproduce the observed blocking-cold spell linkage over North America, despite underestimating the magnitude of blocking frequency. The two ensembles also reproduce the physical drivers that underpin the blocking-cold spell linkage. Spatial agreement with the reanalyses is found in the simulated patterns of temperature advection and surface heat flux forcing anomalies during blocking events. While CanESM5 shows an improved representation of the blocking climatology relative to CanESM2, both yield similar results in terms of the blocking-cold spell linkage and associated internal-variability.

Vitrification of camel skin tissue for use as a resource for somatic cell nuclear transfer in Camelus dromedarius - Young-Bum Son; Yeon Ik Jeong; Yeon Woo Jeong; Xianfeng Yu; Lian Cai; Eun Ji Choi; Mohammad Shamim Hossein; Alex Tinson; Kuhad Kuldip Singh; Singh Rajesh; Al Shamsi Noura; Woo Suk Hwang (In Vitro Cellular & Developmental Biology - Animal, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Mechanistic Deconvolution of Oral Absorption Model with Dynamic Gastrointestinal Fluid to Predict Regional Rate and Extent of GI Drug Dissolution - Alex Yu; Mark J. Koenigsknecht; Bart Hens; Jason R. Baker; Bo Wen; Trachette L. Jackson; Manjunath P. Pai; William Hasler; Gordon L. Amidon; Duxin Sun (The AAPS Journal, 2020)

Soil Properties and Plant Growth Response to Litter in a Prolonged Enclosed Grassland of Loess Plateau, China - Yunwu Xiong; Bing Yu; Mengting Bai; Xueyang Zhang; Guanhua Huang; Alex Furman (Journal of Earth Science, 2019)

Local Application of Autologous Platelet-Rich Fibrin Patch (PRF-P) Suppresses Regulatory T Cell Recruitment in a Murine Glioma Model - Wojciech K. Panek; Katarzyna C. Pituch; Jason Miska; Julius W. Kim; Aida Rashidi; Deepak Kanojia; Aurora Lopez-Rosas; Yu Han; Dou Yu; Catalina Lee Chang; J. Robert Kane; Peng Zhang; et al. (Molecular Neurobiology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

DNA barcoding of vouchered xylarium wood specimens of nine endangered Dalbergia species - Min Yu; Lichao Jiao; Juan Guo; Alex C. Wiedenhoeft; Tuo He; Xiaomei Jiang; Yafang Yin (Planta, 2017)

Mechanistic Fluid Transport Model to Estimate Gastrointestinal Fluid Volume and Its Dynamic Change Over Time - Alex Yu; Trachette Jackson; Yasuhiro Tsume; Mark Koenigsknecht; Jeffrey Wysocki; Luca Marciani; Gordon L. Amidon; Ann Frances; Jason R. Baker; William Hasler; Bo Wen; Amit Pai; et al. (The AAPS Journal, 2017)

MiR-126 Affects Brain-Heart Interaction after Cerebral Ischemic Stroke - Jieli Chen; Chengcheng Cui; Xiaoping Yang; Jiang Xu; Poornima Venkat; Alex Zacharek; Peng Yu; Michael Chopp (Translational Stroke Research, 2017)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Labeling of cynomolgus monkey bone marrow-derived mesenchymal stem cells for cell tracking by multimodality imaging - ZhenHua Ren; JiaYin Wang; ChunLin Zou; YunQian Guan; Yu Alex Zhang (Science China Life Sciences, 2011)

17β-Estradiol Protects Dopaminergic Neurons in Organotypic Slice of Mesencephalon by MAPK-Mediated Activation of Anti-apoptosis Gene BCL2 - Shuyan Wang; Ping Ren; Xiaobo Li; Yunqian Guan; Yu Alex Zhang (Journal of Molecular Neuroscience, 2011)

Chromosomal location and gene paucity of the male specific region on papaya Y chromosome - Qingyi Yu; Shaobin Hou; Roman Hobza; F. Alex Feltus; Xiue Wang; Weiwei Jin; Rachel L. Skelton; Andrea Blas; Cornelia Lemke; Jimmy H. Saw; Paul H. Moore; Maqsudul Alam; et al. (Molecular Genetics and Genomics, 2007)

Quantitative, longitudinal profiling of the primate fecal microbiota reveals idiosyncratic, dynamic communities - Joy Wireman; Mary Lowe; Alex Spiro; Yu‐Zhong Zhang; Andrew Sornborger; Anne O. Summers (Environmental Microbiology, 2006)
Summary We used slot blot hybridization, quantitative polymerase chain reaction (qPCR), and flow cytometry microarrays to quantify specific 16S rDNAs in weekly fecal specimens from four monkeys housed in a research vivarium for periods ranging from five to 8 months. Even in these uniformly housed and fed animals the gut microbiota is idiosyncratic, very dynamic on short timescales, and shows significant positive and negative correlations among some bacteria as well as responses to heavy metal exposure. The relative quantification (fmol targets per total fmol bacterial 16S rDNA) afforded by flow cytometry microarrays agreed well with the absolute quantification (nanogram of target DNA per nanogram of fecal DNA) afforded by slot blots and qPCR. We also noted strengths and weaknesses in inter‐method comparisons for DNA‐based quantification of these complex bacterial communities.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)